Clinical profile and prevalence of women undergoing labor induction under unfavorable conditions at Mont-Amba Hospital Center, Kinshasa, Democratic Republic of the Congo - Nyamungu, Jeannette Imani; Mbongopasi, Bertine Ekeni; Kangite, Jule Moti; Mawunu, Monizi; Ntumba, Joséphine Kankolongo; Koto-Te-Nyiwa Ngbolua, Jean-Paul; Mukandu, Leyka Basua Babintu; Malonga, Françoise Kaj (Orapuh Journal, 2025)
Introduction Despite advances in obstetric care, the practice of artificial induction of labour under unfavourable conditions remains prevalent in low-resource settings, posing heightened risks to maternal and neonatal health. In the Democratic Republic of the Congo (DRC), limited data exist regarding the clinical profile, indications, and outcomes of such inductions. Purpose This study investigated the prevalence, determinants, and obstetric outcomes associated with artificial induction of labour under unfavourable conditions at the Mont Amba Hospital Centre in Kinshasa, DRC. Methods A retrospective cross-sectional study was conducted using maternity records of 336 women who delivered between January and June 2023. Data on socio-demographic, obstetric, and clinical characteristics were extracted and analysed using descriptive statistics, bivariate analysis, and binary logistic regression. Results The prevalence of artificial induction of labour was 26.8%. Significant predictors included a scarred uterus (OR = 3.1; 95% CI: 1.08–9.18), gestational hypertension (OR = 9.2; CI: 2.93–29.16), appendicitis or pelvic cyst history (OR = 7.5; CI: 2.64–21.87), grand multiparity (OR = 11.0; CI: 4.66–26.33), poor antenatal care attendance (<4 visits) (OR = 6.2; CI: 1.45–26.83), placenta previa (OR = 14.7; CI: 4.46–48.80), intrauterine growth restriction (IUGR) (OR = 16.0; CI: 5.36–47.81), and post-term pregnancy (OR = 13.2; CI: 4.00–43.95). Induction often occurred despite unfavourable cervical conditions, with a caesarean section rate of 39.25%. Conclusion Artificial induction of labour is common at Mont Amba Hospital and is frequently performed under suboptimal conditions, contributing to avoidable maternal and neonatal risks. The findings underscore the urgent need to strengthen antenatal care services, standardise induction protocols, and enhance risk-based obstetric management in resource-limited settings.